It is the time! Expectations and experiences of childbirth in pregnant adolescents - Centenaro Levandowski, Daniela (2015)
This longitudinal qualitative study investigated the expectations and experiences related to childbirth of eleven South Brazilian adolescents of low socioeconomic status. They were interviewed in the second trimester of pregnancy and in the baby’s second month. A qualitative content analysis revealed a preference for normal delivery, due to faster recovery, and feelings of fear and anxiety. As for the experience of childbirth, there was a predominance of vaginal deliveries and feelings of happiness, as well as reports of pain. Only a few participants were accompanied by female figures or partners. Both connection and disconnection with the expectations for this event were reported. In general, the finding sindicate a similar scenery to that found among adult mothers.